Eradicating polio in Pakistan: a systematic review of programs and policies. (3rd June 2021) - Ataullahjan, Anushka; Ahsan, Hanaa; Soofi, Sajid; Habib, Muhammad Atif; Bhutta, Zulfiqar A.
ABSTRACT: Introduction : Established in 1994, Pakistan's polio program demonstrated early success. However, despite over 120 supplementary immunization activities in the last decade, polio eradication efforts in Pakistan have been unable to achieve their objective of halting polio transmission. Variable governance, and inconsistent leadership and accountability have hindered the success of the polio program and the quality of the campaigns. Insecurity and terrorism has interrupted polio activities, and community fears and misbeliefs about polio vaccinations continue to persist. Areas covered : The article consists of a systematic review of the barriers and facilitators associated with the delivery of polio eradication activities in Pakistan. We also provide a comprehensive review of the policy and programmatic decisions made by the Pakistan Polio Programme since 1994. Searches were conducted on Embase and Medline databases and 25 gray literature sources. Expert opinion : Polio eradication efforts must be integrated with other preventive health services, particularly immunization services. Addressing the underlying causes of polio refusals including underdevelopment and social exclusion will help counteract resistance to polio vaccination. Achieving polio eradication will require building health systems that provide comprehensive community-centered care, and improving governance and systems of accountability.